A case of fasciitis-panniculitis syndrome successfully treated with etanercept - Roszkiewicz, Jadwiga; Wilkowska, Aleksandra; Maciejewska-Radomska, Agata (Dermatology Review/Przegląd Dermatologiczny, 2009)
Introduction. Fasciitis-panniculitis syndrome (FSP) is a very rare overlap syndrome, combining clinical features of fasciitis eosinophilica and subcutaneous connective tissue inflammation. Histopathological examination reveals dermal thickening, inflammation and fibrosis of the subcutaneous fat, and fibrous thickening of the fascia and the adjacent muscles. In the majority of cases proximal parts of the extremities are affected. Trunk induration is rare. Fasciitis-panniculitis syndrome may be idiopathic or associated with other conditions such as lupus profundus, morphea profunda, eosinophilia–myalgia syndrome, infections and cancer. Patients with FPS are glucocorticosteroid resistant. The efficacy of methotrexate, D-penicillamine, chloroquine, azathioprine and cimetidine is still discussed. Objective. Presentation a severe case of fasciitis-panniculitis syndrome successfully treated with etanercept. Case report. A 52-year-old woman was admitted to our department with pronounced indurations symmetrically involving upper and lower extremities, muscle pain and difficulties in moving. The disease started after hard work in the garden. In laboratory tests significant (54.77%) blood eosinophilia was observed and histopathological examination was characteristic for eosinophilic fasciitis. Therapy with prednisone (30 mg/day) and methotrexate (22.5 mg/week) was ineffective. New lesions of morphea type rapidly involving the whole body and impairment of respiratory function were observed. Pulse therapy with cyclophosphamide (1000 mg every 14 days) followed by PUVA method (for 4 weeks) was not effective. Significant improvement of general condition and remission of indurations were observed during the 24 weeks of therapy with etanercept in a dose of 50 mg s.c. once a week. Conclusion. We believe that etanercept may be regarded as an alternative drug in therapy of severe cases of fasciitis-panniculitis syndrome.